Cancer beliefs in ethnic minority populations: a review and meta‐synthesis of qualitative studies. (12th August 2016) - Licqurish, S.; Phillipson, L.; Chiang, P.; Walker, J.; Walter, F.; Emery, J.
Abstract : People from ethnic minorities often experience poorer cancer outcomes, possibly due to later presentation to healthcare and later diagnosis. We aimed to identify common cancer beliefs in minority populations in developed countries, which can affect symptom appraisal and help seeking for symptomatic cancer. Our systematic review found 15 relevant qualitative studies, located in the United Kingdom (six), United States (five), Australia (two) and Canada (two) of African, African‐American, Asian, Arabic, Hispanic and Latino minority groups. We conducted a meta‐synthesis that found specific emotional reactions to cancer, knowledge and beliefs and interactions with healthcare services as contributing factors in help seeking for a cancer diagnosis. These findings may be useful to inform the development of interventions to facilitate cancer diagnosis in minority populations.